Work-Family Conflict, Happiness and Organizational Citizenship Behavior Among Professional Women: A Moderated Mediation Model - Pan, Ying; Aisihaer, Nadilai; Li, Qinyi; Jiao, Yue; Ren, Shengpei (Frontiers in Psychology, 2022)
This study investigates the association between work-family conflict and organizational citizenship behavior and examines the mediated role of subjective happiness between and moderated part of family support. A moderated mediation model is established based on the Conservation of Resources theory. We collected data from 386 employees of nine companies in China. This study shows that the work-family conflict of female professional employees is negatively correlated with organizational citizenship behavior, and the relationship is mediated by subjective well-being. Furthermore, female professional employees’ family support moderates the effects of work-family conflict on subjective happiness and organizational citizenship behavior, with the relationship weaker when family support is higher. This study enriched the literature on work-family conflict by using family support as a mediating mechanism for work-family conflict. It enhanced understanding the influencing mechanisms of organizational citizenship behavior by constructing a more detailed model.